On the persistence and detectability of ancient Beothuk mitochondrial DNA genomes in living First Nations peoples. (2nd January 2019) - Collier, Ashley; Carr, Steven M.
Abstract: Claims have long been made as to the survival to the present day of descendants of the Newfoundland Beothuk, a group generally accepted to have become extinct with the death of the last known member, Shanawdithit, in 1829. Interest has recently been revived by the availability of commercial genetic testing, which some claim can assign living individuals to specific Native American groups. We compare complete mitogenome sequences (16569 bp) from aDNA of eight distinct Beothuk lineages, including Shanawdithit's uncle Nonosabasut and his wife Demasduit, with three Newfoundland Mi'kmaq lineages and 21 other living Native Americans drawn from GenBank. A Newfoundland Mi'kmaq lineage in Haplogroup A is more similar to three Native Americans (1–3 SNPs) than to the most closely related Beothuk (24 SNPs). Nonosabasut in Haplogroup X is identical to a non-Beothuk Native American. Demasduit in Haplogroup C differs from three other Native Americans by 1–4 substitutions. Within a 2168 bp region of the HVS sequences available from living Mi'kmaq of the Miawpukek First Nation in Newfoundland, lineages in Haplogroups C, X, and A differ by 1, 4, and 8 substitutions, from the most similar Beothuk, and are more similar to other Native Americans. MtDNA genome sequences in living persons identical or similar to those of Beothuk do not necessarily indicate Beothuk ancestry. Mi'kmaq lineages cannot at this time be associated with any Beothuk lineages more closely than those of other Native Americans.